A kind of heat-insulating and waterproof polyimide aerogel and preparation method thereof

By using directional freezing and heat treatment processes in polyimide aerogels, combined with polyimide microfiber, polyamide imide nanofiber and bismaleimide, the problems of insufficient thermal insulation and poor mechanical properties in the prior art are solved, and efficient thermal insulation and waterproofing performance are achieved.

CN118667222BActive Publication Date: 2025-04-11TIANJIN POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410981736.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2025-04-11
Estimated Expiration
2044-07-22

AI Technical Summary

Technical Problem

The existing polyimide aerogels have insufficient thermal insulation performance in high temperature and humid environments, poor mechanical properties, long preparation period and low efficiency.

Method used

Polyimide microfiber, polyamide imide nanofiber and bismaleimide are homogeneously dispersed in alcohol solvents, and heat-insulated and waterproof polyimide aerogel is prepared after directional freezing and heat treatment.

Benefits of technology

It achieves high flame retardant, high temperature resistance, excellent compression performance, thermal insulation performance and waterproof performance, which is suitable for thermal insulation needs in a variety of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118667222B_ABST
    Figure CN118667222B_ABST
Patent Text Reader

Abstract

The present invention provides a heat-insulating and waterproof polyimide aerogel and a preparation method thereof. The preparation method comprises the following steps: homogeneously dispersing polyimide micron fibers, polyamide-imide nanofibers and bismaleimide in an alcohol solvent to obtain a mixed dispersion; the mixed dispersion is subjected to directional freezing and heat treatment to obtain the heat-insulating and waterproof polyimide aerogel; wherein the mass ratio of the polyimide micron fibers to the polyamide-imide nanofibers is 1:7-3:1. The preparation method is simple and efficient to operate, and is suitable for large-scale production; the prepared aerogel has high flame retardancy, high temperature resistance, and excellent compression performance, heat insulation performance and waterproof performance, and can meet the heat insulation requirements of various application scenarios.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat-insulating materials, and in particular to a heat-insulating and waterproof polyimide aerogel and a preparation method thereof. Background Art

[0002] The unique three-dimensional network structure of aerogel gives it high porosity, low density, high specific surface area, low thermal conductivity, low dielectric constant and other characteristics, making it show potential for application in aerospace, military equipment, fire safety and other fields. In the field of fire safety, fire protection clothing with excellent high temperature resistance, flame retardancy and heat insulation thermal protection performance is crucial for maintaining the safety of personnel in various environments, especially in the face of fire environments.

[0003] As a new type of polymer material, polyimide has attracted extensive attention from researchers due to its excellent thermal properties. Currently, a variety of polyimide aerogels have been used for high-temperature thermal insulation materials, but they still face problems such as further improvement of thermal insulation performance, poor mechanical properties, long preparation cycle, and low efficiency. Therefore, it is urgent to develop a polyimide aerogel with lightweight, excellent thermal insulation and waterproof properties, so as to provide stronger safety protection for firefighters working in high temperature and humid environments. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention discloses a polyimide aerogel with high flame retardancy, high temperature resistance, excellent compression performance, thermal insulation performance and waterproof performance, and a preparation method thereof. The aerogel can meet the thermal insulation requirements of various application scenarios.

[0005] In order to achieve the above technical objectives, on the one hand, the present invention proposes a method for preparing a heat-insulating and waterproof polyimide aerogel, which comprises homogeneously dispersing polyimide (PI) micron fibers, polyamide-imide (PAI) nanofibers and bismaleimide (BMI) in an alcohol solvent to obtain a mixed dispersion; the mixed dispersion is subjected to directional freezing and heat treatment to obtain the heat-insulating and waterproof polyimide aerogel; wherein the mass ratio of the polyimide micron fibers to the polyamide-imide nanofibers is 1:7-3:1.

[0006] In the above technical solution, three polyimide materials containing imide functional groups are used as raw materials, and aerogels are obtained by directional freezing and heat treatment. Among them, BMI, as a cross-linking agent, undergoes a cross-linking reaction during heat treatment, which causes the micro-nano fibers to interact with each other, thereby enhancing the interface effect between the micro-nano fibers and showing excellent mechanical properties of the aerogel. In addition, the above technical solution uses PI micron fibers and PAI nanofibers with very different diameters to prepare aerogels, and under the action of the cross-linking agent, a rigid-flexible coupling structure of the aerogel microstructure is formed, which improves the compression performance of the aerogel.

[0007] In the above technical scheme, the freezing method of the mixed dispersion also directly affects the comprehensive performance of the prepared aerogel. Based on exploratory experiments, the research and development team of the present invention found that if the mixed dispersion is directly placed in a freezing device and ice crystals are allowed to grow randomly, the dispersion may be stratified or the aerogel structure may be unstable. The above technical scheme adopts a directional freezing method to make the ice crystals grow from bottom to top in a single directional direction. Since the diameters of PI micron fibers and PAI nanofibers are very different, during the directional freezing process, the PI micron fibers with larger fiber volume and weight hinder the directional growth and growth rate of ice crystals, further reducing the probability of ice crystals melting during the freezing casting process. The flaky secondary pore walls formed thereby are tortuous and the secondary pore diameters are small, which is more helpful in reducing gas heat conduction. The excellent thermal insulation and compression properties of the waterproof and heat-insulating aerogel of the present invention were verified through performance testing in the embodiments of the present invention.

[0008] In a further example of the present invention, technical features such as the mass ratio of the PI micron fibers and the PAI nanofibers, the diameter range of the PI micron fibers and the PAI nanofibers, the control conditions of the directional freezing, the type of the organic solvent, and the addition of a waterproofing agent during the preparation process to enhance the waterproof performance of the aerogel were explored and optimized, thereby further enhancing the waterproof, thermal insulation and mechanical properties of the aerogel to provide a product that meets the thermal performance and waterproof performance requirements of fire protection.

[0009] On the other hand, the present invention provides a heat-insulating and waterproof polyimide aerogel prepared by the above-mentioned preparation method.

[0010] Compared with the prior art, the present invention uses three polyimide materials as raw materials, obtains aerogels through directional freezing and heat treatment, and the imide functional groups between the raw materials enhance the interface between micro-nano fibers and improve the mechanical properties of the aerogels; BMI acts on PI micron fibers and PAI nanofibers with a large diameter difference through thermal polymerization, and the microstructure of rigid-flexible coupled aerogels is obtained in combination with the directional freezing process. The preparation method is simple and efficient to operate, and is suitable for large-scale production; the prepared aerogels have high flame retardancy, high temperature resistance, and excellent compression performance, thermal insulation performance and waterproof performance, which can meet the thermal insulation requirements of various application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0012] Figure 1 The electron microscope morphology images of PIMNFA-0, PIMNFA-50 and PIMNFA-100 aerogels in Example 2 are shown;

[0013] Figure 2 A comparison of the thermal insulation properties of different PI aerogels in Example 2 is shown;

[0014] Figure 3 The compression cycle performance of different PI aerogels in Example 2 is shown;

[0015] Figure 4 The results of the 1000 loading and unloading fatigue compression test of the PIMNFA-50 aerogel in Example 2 are shown;

[0016] Figure 5 The thermogravimetric analysis results of different PI aerogels in Example 2 are shown;

[0017] Figure 6 The flame retardant performance test process of PIMNFA-50 aerogel in Example 2 is shown;

[0018] Figure 7 A comparison chart of the waterproof performance of the thermal insulating and waterproof PI aerogel in Example 3 is shown. DETAILED DESCRIPTION

[0019] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below, and preferred embodiments of the present invention are given. However, it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, i.e., not intended to limit the scope of protection of the present invention.

[0020] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0021] Example 1

[0022] A method for preparing a heat-insulating and waterproof polyimide aerogel, comprising the steps of homogeneously dispersing polyimide (PI) micron fibers, polyamide-imide (PAI) nanofibers and bismaleimide (BMI) in an alcohol solvent to obtain a mixed dispersion; subjecting the mixed dispersion to directional freezing and heat treatment to obtain the heat-insulating and waterproof polyimide aerogel; wherein the mass ratio of the polyimide micron fibers to the polyamide-imide nanofibers is 1:7-3:1.

[0023] It should be noted that the present invention does not limit the specific operation of homogenous dispersion. Those skilled in the art can determine the appropriate homogenization method according to the actual working conditions. For example, the PI micron fibers can be homogenously dispersed in an organic solvent first, and then PAI nanofibers and BMI powder can be added and continued to be homogenously dispersed to obtain a mixed dispersion; or the PI micro-nano fibers, PAI nanofibers and / or BMI powder can be homogenously dispersed separately, and finally mixed to obtain a mixed dispersion. The technical solutions thus formed are all within the protection scope of the present invention.

[0024] The mass ratio of the sum of the mass of the PI micron fibers and the PAI nanofibers to the mass of the BMI powder is (4-6):1, preferably 5:1.

[0025] It should be noted that the sources of the PI micron fibers, PAI nanofibers and BMI in this embodiment are not limited, and those skilled in the art can choose to obtain them by commercial purchase or self-preparation, and the technical solutions formed thereby are all within the protection scope of the present invention. In a preferred example of this embodiment, the PAI nanofibers are prepared by an electrospinning process, and the PAI nanofiber membrane obtained by electrospinning can be cut into small pieces of nanofiber membrane for standby use before use.

[0026] It should be noted that those skilled in the art may choose to use an organic solvent to wash and dry the raw materials before preparing the mixed dispersion to remove oil stains, dust, etc. on the surface of the raw materials; the organic solvent used may be one or both of ethanol and acetone.

[0027] Optionally, the diameter range of the polyimide micron fiber can be 12-17.4 μm, and the diameter range of the polyamide-imide nanofiber can be 200-1000 nm. The diameter difference between the PI micron fiber and the PAI nanofiber used in this embodiment is very large. By optimizing the diameter range of the two, the mechanical properties of the aerogel can be enhanced.

[0028] The R&D team explored the control conditions of directional freezing. Optionally, liquid nitrogen is used for directional freezing in the directional freezing operation; the directional freezing time can be selected to be 8 to 30 minutes. The R&D team found in the early exploration that when an ordinary freezer (about -20°C) is used for directional freezing of the dispersion, stratification occurs after about 2 hours, which will directly affect the subsequent volume and performance of the aerogel; and the use of liquid nitrogen directional freezing in this embodiment can not only improve the preparation efficiency, but also make the microstructure of the aerogel produced uniform and stable.

[0029] Optionally, the mixed dispersion is poured into a mold for directional freezing. Further optionally, the mold is made of metal and polytetrafluoroethylene materials to adapt to the liquid nitrogen directional freezing temperature and prevent the occurrence of mold cracking and other working conditions.

[0030] Optionally, the heat treatment temperature is 180-220° C. and the heat treatment time is 1-2 hours, which provides suitable reaction conditions for the cross-linking reaction of the cross-linking agent BMI.

[0031] Optionally, the alcohol solvent is selected from tert-butyl alcohol or tert-butyl alcohol aqueous solution. Further optionally, the volume ratio of tert-butyl alcohol to water in the tert-butyl alcohol aqueous solution is 1:(2-5), preferably 1:4.

[0032] Example 2

[0033] Based on the preparation method of the heat-insulating and waterproof polyimide aerogel shown in Example 1, this example optimizes the mass ratio of the PAI nanofibers and the PI microfibers. It should be noted that the specific process flow shown in this example is only a preferred display and does not limit the scope of protection of the present invention.

[0034] The PI micron fibers used in this embodiment were purchased from Hubei Tengdi New Materials Co., Ltd., with diameters ranging from 12 to 17.4 μm and an average diameter of about 14.62 μm; the PAI nanofibers used were prepared by electrospinning, with diameters ranging from 209.6 to 531.5 nm and an average diameter of about 346.67 nm.

[0035] Specifically, S1: 0g, 0.15g, 0.3g, 0.45g and 0.6g of PI micron fiber are placed in 100ml dispersion respectively, the homogenization speed of high-speed homogenization is 15000-20000rad / min, the homogenization time is 10-30min, and PI micron fiber dispersion is prepared. Then, correspondingly, 0.6g, 0.45g, 0.3g, 0.15g and 0g of PAI micron fiber and 0.12g of bismaleimide powder are placed in polyimide dispersion respectively, the homogenization speed is 10000-15000rad / min, the homogenization time is 1-5min, and a mixed dispersion is prepared.

[0036] It should be noted that the present embodiment does not limit the specific operation of homogeneous dispersion, and those skilled in the art can determine the end point of homogeneous dispersion by observing the state of the mixed dispersion, and the homogeneous state of the mixed dispersion can be selected as the end point of homogeneous dispersion.

[0037] S2: PI aerogels were obtained by liquid nitrogen directional freezing and heat treatment. According to the percentage of PI micron fibers in the total amount of micro-nano fibers, they were marked as PIMNFA-0, PIMNFA-25, PIMNFA-50, PIMNFA-75, and PIMNFA-100.

[0038] In the specific freezing process, the mixed dispersion is placed in a mold, and the bottom of the mold is attached to a copper block in liquid nitrogen. The directional freezing time depends on the size of the mold; the freezing time is in the range of 8 to 30 minutes. When the surface of the dispersion in the mold is frozen and solidified, the freezing is completed.

[0039] In the specific heat treatment process, the appropriate heat treatment temperature causes the crosslinking agent BMI between the micro-nano fibers to undergo a polymerization reaction, forming an interface effect between the fibers, and giving the polyimide aerogel excellent mechanical properties. Optionally, the heat treatment temperature is 180-220°C, and the heat treatment time is 1-2 hours. It should be noted that the heat treatment time depends on the size of the prepared sample.

[0040] Figure 1 The electron microscope morphology of PI aerogels prepared by PIMNFA-0, PIMNFA-50 and PIMNFA-100 is shown. Through comparative analysis, it can be seen that PIMNFA-0 is a sheet-like nanofiber network, forming connected tunnels and larger holes; while the tunnels formed by PIMNFA-50 are circuitous and the holes are smaller. It is speculated that the large volume and weight of PI micron fibers hinder the directional growth and growth rate of ice crystals, thereby reducing the probability of ice crystal fusion during the freezing casting process, but excessive micron fiber dispersion will cause micron fiber aggregation, so that PIMNFA-100 has higher pore connectivity and larger voids.

[0041] Furthermore, this example tested the thermal insulation properties of different PI aerogels, and the results were as follows: Figure 2 Thermal conductivity measurement: The results were analyzed by a hot disk tester, and the test standards used were: ISO22007-2.2; GBT32064-2015. The thermal insulation performance comparison was performed by measuring the thermal conductivity of the five groups of samples in the experiment, and then the average value was taken after repeated testing of the five groups.

[0042] By comparison, it can be seen that when the mass ratio of PI microfibers to PAI nanofibers is 1:1, the thermal conductivity of the obtained heat-insulating and waterproof PI aerogel is the lowest, which is 26.9 mW·m -1 K -1 . Combined Figure 1The thermal conductivity of aerogel is jointly contributed by thermal convection, thermal radiation, solid conduction and gas conduction. Since the pore size of the prepared PI aerogel is much lower than 1 mm, thermal convection can be ignored. PIMNFA-0 and PIMNFA-100 aerogels have large-void connection tunnels, and insufficient dissipation of radiation waves leads to their high thermal radiation. At the same time, a larger number of nanofibers and a larger contact area of ​​micron fibers increase solid conduction, thereby causing a decrease in the thermal conductivity of both. The heat-insulating and waterproof PI aerogel of the present invention has a unique bridging structure between the micro-network formed by the PI micron fibers and the PAI nanofibers, thereby reducing solid conduction. That is, the synergistic effect of this rigid-flexible coupling structure enhances the thermal insulation performance of the heat-insulating and waterproof PI aerogel of the present invention.

[0043] Furthermore, this embodiment tested the compression cycle performance of 5 PI aerogels. The specific operation is: under a strain of 60%, the PI aerogel is subjected to a compression cycle test. In the range of strain < 60%, the test results are as follows: Figure 3 As shown; it can be seen that PIMNFA-50 exhibits the highest compression modulus.

[0044] Furthermore, this example tests the compression fatigue resistance of PIMNFA-50 aerogel. Figure 4 The results of 1000 loading and unloading fatigue compression tests on PIMNFA-50 are shown. The results show that when the strain is 50% and the loading rate is 60mm / min, only 10.87% plastic deformation is produced after 1000 compressions, and the maximum stress retention rate is 71.6%, reflecting good compression recovery performance, which formally proves that the heat-insulating and waterproof PI aerogel with a rigid-flexible coupling structure of the present invention can be used for a long time.

[0045] Furthermore, this example tests the high temperature resistance of polyimide aerogels and performs thermogravimetric analysis on different PI aerogels. Figure 5 As shown, when PIMNFA-50 aerogel loses 5% of its weight, the corresponding temperature is 441.8°C, which is much higher than other polymer materials, indicating that it has excellent high temperature resistance.

[0046] Furthermore, this example tests the flame retardant properties of sample PIMNFA-50. Figure 6 The flame retardant performance test process of PIMNFA-50 aerogel is shown, and the combustion process and state are characterized by the combustion photo (combustion state) and the thermal imaging camera picture (combustion temperature). Figure 6 It can be confirmed that when the PIMNF-50 aerogel comes into contact with the flame, it burns; when the PIMNFA-50 aerogel is separated from the flame, it quickly extinguishes itself, no droplets are formed, and only a small amount of smoke is produced, showing excellent flame retardant properties.

[0047] From the above analysis, it can be seen that the mass ratio of the polyimide micron fiber to the polyamide-imide nanofiber in the technical solution of the present invention can be selected as 1:7-3:1, further selected as 1:3-3:1, further selected as 3:5-5:3, and further selected as 1:1.

[0048] Example 3

[0049] The preparation method shown in this embodiment is the same as the preparation method of PIMNFA-50 heat-insulating and waterproof polyimide aerogel shown in Example 2, except that a waterproofing agent is added when preparing the mixed dispersion in this embodiment. Optionally, the waterproofing agent is at least one of a silicone waterproofing agent, an acrylate waterproofing agent, and a paraffin waterproofing agent.

[0050] In an optional solution of this embodiment, the waterproofing agent used is acrylic waterproofing agent PM-388, 8014F purchased from Guanyou Chemical Technology Co., Ltd.

[0051] like Figure 7 The waterproof properties of the prepared thermal insulating and waterproof polyimide aerogel (labeled as PIMNFS-0, PIMNFS-2.5, PIMNFS-5, PIMNFS-7.5, PIMNFS-10, respectively) are shown when the added volume of the waterproofing agent is 0%, 2.5%, 5%, 7.5% and 10% of the volume of the mixed dispersion, respectively, and the contact angle is measured using a contact angle meter.

[0052] Depend on Figure 7 It can be confirmed that the heat-insulating and waterproof polyimide aerogel of the present invention has excellent waterproof performance. When the amount of the waterproofing agent added is 7.5% of the volume of the mixed dispersion, the water contact angle is 138.96°, but when the amount added continues to increase, the growth trend of the waterproof performance slows down. Therefore, the volume content of the waterproofing agent in the mixed dispersion can be selected to be no more than 10%, further selected to be 7.5%-10%, and further selected to be 7.5%.

[0053] It should be noted that the above contents are further detailed descriptions of the present invention in combination with specific implementation methods, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions; the dimensional data of this embodiment does not necessarily limit the technical solution, but only shows one of the specific working conditions. For ordinary technicians in the technical field to which the present invention belongs, several simple improvements and modifications can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.

Claims

1. A method for preparing a heat-insulating and waterproof polyimide aerogel, characterized in that: Polyimide micron fibers, polyamide-imide nanofibers and bismaleimide are homogeneously dispersed in an alcohol solvent to obtain a mixed dispersion; the mixed dispersion is subjected to directional freezing and heat treatment to obtain the heat-insulating and waterproof polyimide aerogel; wherein the mass ratio of the polyimide micron fibers to the polyamide-imide nanofibers is 1:7-3:1; liquid nitrogen is used for directional freezing in the directional freezing operation; and the directional freezing time is 8 to 30 minutes.

2. The method for preparing the heat-insulating and waterproof polyimide aerogel according to claim 1, characterized in that: The mass ratio of the polyimide micron fiber to the polyamide-imide nanofiber is 1:3-3:

1.

3. The method for preparing the heat-insulating and waterproof polyimide aerogel according to claim 2, characterized in that: The mass ratio of the polyimide microfiber to the polyamide-imide nanofiber is 1:

1.

4. The method for preparing the heat-insulating and waterproof polyimide aerogel according to claim 1, characterized in that: The diameter of the polyimide microfiber is in the range of 12-17.4 μm, and the diameter of the polyamide-imide nanofiber is in the range of 200-1000 nm.

5. The method for preparing the heat-insulating and waterproof polyimide aerogel according to claim 1, characterized in that: The heat treatment temperature is 180-220° C., and the heat treatment time is 1-2 hours.

6. The method for preparing the heat-insulating and waterproof polyimide aerogel according to claim 1, characterized in that: The alcohol solvent is selected from tert-butanol or tert-butanol aqueous solution.

7. The method for preparing the heat-insulating and waterproof polyimide aerogel according to claim 1, characterized in that: A waterproofing agent is added to the mixed dispersion.

8. The method for preparing the heat-insulating and waterproof polyimide aerogel according to claim 7, characterized in that: The waterproofing agent includes one or more of an organosilicon waterproofing agent, a polyurethane waterproofing agent, and a paraffin waterproofing agent; the volume content of the waterproofing agent in the mixed dispersion is no more than 10%.

9. The heat-insulating and waterproof polyimide aerogel prepared according to the preparation method according to any one of claims 1 to 8.